2012
DOI: 10.1166/jnn.2012.5928
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Nanocomposites of High Refractive Index Based on Epoxy Resin and TiO<SUB>2</SUB> Nanoparticle

Abstract: A stepwise sol-gel method for the synthesis of stable colloidal TiO2 using hydrolysis and condensation reactions of titanium tetraisopropoxide (TTP) was investigated. The surface modification was carried out using 3-glycidoxypropyltrimethoxysilane (GPTMS). The particle size range of the modified TiO2 observed by TEM was 3-8 nm. The nanocomposites based on an epoxy resin and the modified TiO2 showed strong UV absorption, but maintained high transmittance within the visible region. TEM images of the nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…USW) shown a less yellowness index than the control film. However, when exposed to UV radiation, it was observed that TiO 2 particles dispersed with ultrasound caused a slight increase in the yellowness index [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…USW) shown a less yellowness index than the control film. However, when exposed to UV radiation, it was observed that TiO 2 particles dispersed with ultrasound caused a slight increase in the yellowness index [ 41 ].…”
Section: Resultsmentioning
confidence: 99%